Nurturing the culture of student participation through online reflection using the QR code system - Mohd Fauzi Mohd Yunus; Aspalilla Main (RedWhite Press, 2020)
Participation of student in reflection shows an important role in improving learning strategies. However, the common reflection practice focuses only on self-reflection and it becomes unauthentic. This innovation therefore attempted to prepare the platform for student’s reflection towards the teaching and learning activities in class using online reflection system. Hence an online reflection system based on QR code was developed to reflect this scenario. The code successfully accesses the system and allow the written reflection. Testing result shows the 100% efficiency of QR code recognition and excellence result for inter-rater reliability analysis by experts respectively.